Agama, Budaya dan Wajah Kita: Membaca Hasil Musyawaran SVD Sejagad 2006 - Sudhiarsa, Raymundus I Made (Perspektif, 2006)
Mission is basically a business of transformation. Christian community, as a community of the disciples, participates in mission, namely transformation of the world as God wants it to be. Society of the Divine Word (SVD), as one of the Missionary Societies within the Catholic Church, was founded to participate in this 'missio Dei' (God's mission). In principle members of the Society have committed themselves to be participants in this divine business, work of salvation. This article tries to highlight some issues of transformation which have been formulated by the XVI General Chapter of the Society held in Rome, June 4- July 8, 2006. The writer tries to look at them from an Indonesian perspective and looks for ways of their implementation. He considers that it could significantly be done in the SVD's communities which are, says the General Chapter, best regarded as 'schools of dialogue'. Precisely in these communities issues of transformation in line with the gospel values should be elaborated in ga such a way that the members are being revitalized time and again. In so doing, missionaries can grow more and more in the spirit of prophetic dialogue and become as St. Paul says - "everything for everyone" (cf. 1Cor 9:19).